Gonrang dan Gual dalam Dinamika Masyarakat Simalungun - Wiflihani, Wiflihani (Universitas Negeri Medan, 2015)
This writing purposes to understand on the musical instrument of gonrang in social dynamic of Simalungun people. As an ensemble, gonrang of Simalungun plays a significant role in the funeral ceremony. The main fuction of the percussion instrument is to summon the spirit of ancestors for advices and blessing. For Simalungun people, there are two gonrangs which is known, namely gonrang sipitu-pitu or gonrang bolon and gonrang sidua-dua dagang. However, the common term in accompanying a song for gonrang musical ensemble is gual.